THORACIC SURGERY: PRESENT-DAY PROBLEMS AND PROSPECTS OF DEVELOPMENT - Шкурупій, О.А. (World of Medicine and Biology, 2015)
Nowadays, the diseases of respiratory system is the actual problem for health care system of Ukraine. It is the most common pathology in the structure of morbidity of our population. Most patients of this category require conservative treatment of the therapeutic profile. However, the proportion of patients that require operative thoracic surgery treatment grows every year. They are the patients with a variety of destructive processes of infectious origin in the lungs, bronchiectasis, pneumomycosis, benign and malignant tumors of the lungs and pleura, tuberculosis, pleuritis, etc. In addition to operations on the lungs, thoracic surgeons perform reconstructive operations on the heart and vessels with diseases of different etiology, carry out surgical treatment of ischemic heart disease and its complications, conduct surgeries for infective endocarditis and similar problems. Surgery of the mediastinum, esophagus and diaphragm is also in the focus of thoracic surgery. The aim of our study was the analysis of medical literature, that covered the present state of thoracic surgery in Ukraine and in the world and prospects of its development. Although the achievements of reconstructive surgery of the thoracic cavity organs are undeniable, further successful development of thoracic surgery is possible only providing comprehensive approach to improve diagnosis and resuscitation, to eliminate postoperative complications in this field of medicine. Also, endoscopic surgery fundamentally altered approaches to the treatment of many diseases of thoracic cavity organs over the past two decades. Nowadays, videothoracoscopic surgery became the "gold standard" in the treatment of numerous pathologies of the thoracic cavity organs. Videothoracoscopy is performed under general anesthesia with separate intubation of two main bronchi. Portable video camera and two video monitors are also used, allowing surgeons to be opposite each other. The operation is usually performed on the patient lying on his/her side with the roller under the thorax. Thoracoports with the diameter of 5, 10, 12 mm are the most commonly used in such cases. Videothoracoscopic operations have several advantages in comparison with thoracotomy: they are less traumatic, not complicated by significant bleedings, reduce the need for analgesics and intensive therapy in the postoperative period, do not disturb respiratory function significantly, reduce hospital stay. Nowadays, indications for videothoracoscopy have increased significantly. They are pleural effusion of different etiology, interstitial lung diseases, neoplasms of the peripheral parts of the lungs and pleura, diseases of the mediastinum and pericardium, closed and open injuries of the thoracic wall, with hemothorax, chilothorax, pneumothorax, pyopneumothorax, examination of intrathoracic lymph nodes in malignant tumors of adjacent organs and similar cases. Videothoracoscopy is actively introduced in clinical practice by the staff of the National Institute of Phthisiology and pulmonology named after. F. G. Yanovsky, as evidenced by the number of published informative papers in 2015. Special attention to videothoracoscopy is explained by potential prospects of this progressive method of thoracic pathology surgical treatment. Currently, surgical technique of thoracic surgery is constantly improving, so it is equally harmful both the decision to perform the operation necessarily using videothoracoscopy and unreasonable refusal in favor of open surgery. Conclusions. Nowadays, thoracic surgery is characterized by rapid development due to introduction of new advanced methods of diagnosis and treatment. Continuous improvement of techniques of such modern surgery methods as videothoracoscopy promotes opportunities for their implementation.